Titania and titania-silver nanocomposite coatings grown by electrophoretic deposition from aqueous suspensions - Santillan, M. J.; Quaranta, N. E.; Boccaccini, Aldo R. (Surface & Coatings Technology, 2010)
This study focused on the synthesis of titania-silver (TiO2-Ag) nanocomposite coatings with potential enhanced antibacterial properties for applications in orthopedic implants. Ag nanoparticles (4nm) were grown directly on the surface of commercially available TiO2 nanoparticles (23nm) by nucleophilic reaction. The electrophoretic deposition (EPD) of TiO2 and TiO2-Ag nanoparticles on titanium substrates using aqueous suspensions was investigated. Best results were achieved by using water and ethanol as co-solvents. The EPD process (voltage: 3V, deposition time: 90s) led to TiO2 based coatings on titanium substrates exhibiting homogeneous and uniform microstructure. In vitro bioactivity tests in Kokubo's simulated body fluid (SBF) to evaluate the formation of hydroxyapatite (HA) on the coating surface were performed. The results showed that the extent of HA formation rapidly increased with increasing time in SBF and it decreased as silver amount in the coating increased. XRD, TEM and SEM-EDAX were used to investigate the microstructure of the nanomaterials and coatings. The high bioactivity of the TiO2 based electrophoretic coatings indicates their potential for use as bioactive antibacterial layers in orthopedic implants. © 2010 Elsevier B.V.
UnivIS-Import:2015-03-09:Pub.2010.tech.IW.LM.titani
Keywords: Antibacterial coatings; Biomedical applications; Electrophoretic deposition; Silver nanoparticles; Titania coatings